Diagnostic and treatment algorithm for anaphylactic shock of the Self-regulatory organization of the “National board of phlebologists” Association - article Editorial (Амбулаторная хирургия)
Many phlebologists today work in ambulatory settings, using both local anesthetics and sclerosants. Cases of anaphylactic shock are rare, but its consequences can be catastrophic. At the request of the self-regulatory organization of the “National College of Phlebologists” Association with the support of “Servier” company, the legal partner of the LLC “Faculty of Medical Law” board, together with leading anesthesiologists-resuscitators, has developed an easy-to-understand and easy-to-deliver information Algorithm for the diagnosis and treatment of anaphylactic shock. This algorithm will not only reduce the risks of adverse effects of anaphylaxis for the patient, but will also protect the physician in case of litigation, as it is prepared with references to current sources of evidence-based medical practice and regulations.